Água, desenvolvimento e injustiça ambiental: uma análise crítica da Barragem Castanhão no Ceará - Alves, Marina Calisto (2023)
This work seeks to analyze the implementation process of the Castanhão Dam, in Ceará, as a water development policy responsible for redesigning territories in the semi-arid northeast, in order to present a critique about the construction and operation of this work, highlighting the production of injustices and environmental conflicts and evaluating the effectiveness of social compensation policies implemented among affected populations. It starts from the understanding that the construction of large water works in Brazil has historically inhabited the universe of national and regional developmental policies, especially in the Brazilian Northeast. When managing water resources, providing a type of material and symbolic enclosure of water, these works cause a set of environmental impacts in a broad sense, reverberating in consequences for the affected populations and in conflicts regarding access to water. Thus, the empirical basis for the analyzes presented here comprises the families affected by the Castanhão Dam and who reside in resettlement areas in the territorial area of influence of the work. Methodologically, the research was carried out through an interdisciplinary approach and with a qualitative focus, using resources such as bibliographical research, document analysis, interviews, and steps of the Agricultural Systems Diagnostic Analysis Methodology (ADSA). In this way, it was identified that the families affected by the Castanhão Dam, and who reside in the geographical area close to the dam, experience a process of marked water insecurity, whether with regard to water for human consumption or for agricultural production, configuring a scenario of environmental injustice, and, specifically, of water injustice, and that, in addition, the social compensation policies established by the institutional actors involved in the construction of the work did not show the expected effectiveness, having several contradictions and insufficiencies. This situation is responsible for configuring an unequal distribution of access to water and the benefits of dam construction, revealing a scenario of socio-ecological debt towards the affected region.